Assesment of the development of European Air Forces in the context of US-China competition - Jan Feryna; Libor Kutěj (Vojenské rozhledy, 2023)
The air force plays an important role in armed conflicts. It was no different in the Odyssey Dawn and Unified Protector operations in Libya in 2011. The European dependence on the US became fully apparent during those operations. After 2011, US attention has been shifted to Asia. This article focuses on the evaluation of the development of European air forces from 2011 to 2021 in the context of the shift of US attention to Asia. The article uses a dataset to compare the number of aircraft in specific categories in 2011 and 2021. The research shows that European states maintain a fleet of around 2,000 fighter jets, while compared to 2011, the number of ISR aircraft decreased from 183 to 122 and the number of air-to-air refuelling aircraft from 70 to 67. In contrast, the number of MALE unmanned vehicles has doubled from 45 to 91. However, in the context of the US shift Asia, those numbers are insufficient, and European states are still dependent on US support.